2021
DOI: 10.1111/lam.13607
|View full text |Cite
|
Sign up to set email alerts
|

8‐hydroxyquinoline and quinazoline derivatives as potential new alternatives to combat Candida spp. biofilm

Abstract: Significance and Impact of the Study: Infections related to central venous catheters associated with Candida spp. colonization and biofilm formation have high rates of morbidity and mortality, mainly due to the absence of targeted and specific treatment. We believe that this work is a very important step in advancing research on the management and treatment of these infections, which are so serious. The tested compounds showed a promising character against the tested Candida spp. strains. Furthermore, the use … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Previous studies have shown that indole analogues [ 52 ] and quinazoline derivatives [ 53 ] can inhibit the formation of biofilm and hyphae of C. albicans . Our findings also indicated that the structural features of diaryl chalcogenides contribute to their biological activities.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that indole analogues [ 52 ] and quinazoline derivatives [ 53 ] can inhibit the formation of biofilm and hyphae of C. albicans . Our findings also indicated that the structural features of diaryl chalcogenides contribute to their biological activities.…”
Section: Discussionmentioning
confidence: 99%
“…Its antitumor effect has mainly been associated with its ability to modulate oxidative stress, inflammation, platelet aggregation, and the induction of tumor cell apoptosis [ 11 , 12 , 13 ]. On the other hand, 8-hydroxyquinoline is a heterocyclic organic compound known to be a chelating agent with antimicrobial and anticancer activity [ 14 , 15 , 16 , 17 ]. Specifically, its anticancer activity has been associated with its possible ability to inhibit the proliferation and migration of cancer cells through the induction of apoptosis and the generation of ROS, among other mechanisms [ 18 , 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%